PENGEMBANGAN DAKWAH ALKHAIRAAT DI KOTA PALU - Nur, Minan (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
The development of Islamic preaching carried out by Alkhairaat Palu has been influenced by dynamic economic struggle ( mareso masagena ), flexible local culture ( nosampesuvu ), and the wisdom of community’s leader either formal or informal ( tataguna ). Alkhairaat is an Islamic preaching institution that perform activities in such fields as preaching, education, and economic. This research used phenomenology in observing activities of preaching done by Alkhairaat influenced by the spirit of organization, which serves as nomena . The programs of Alkhairaat are explicitly expressed, while the ideological spirit of Guru Tua (the Old Teacher) is implicitly considered. The management of Alkhairaat is implemented from the central to local areas. The effectiveness of organization wheel is focused on the development of Islamic preaching, while the goal is to ensure the implementation of Islamic doctrines for Muslim community in accordance with the Quran and Sunnah.